2012
DOI: 10.1111/pcn.12002
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between atrophy of the entorhinal cortex and cognitive function in patients with Alzheimer's disease and mild cognitive impairment

Abstract: Aims:In order to confirm the utility of the voxelbased specific regional analysis system for Alzheimer's disease (VSRAD) in assessing the atrophy of the entorhinal cortex, we investigated whether there were correlations between VSRAD and the scores of neuropsychological tests in the patients with Alzheimer's disease (AD) and mild cognitive impairment.Methods: Thirty patients, including 18 AD and 12 mild cognitive impairment patients, were included in this study. VSRAD was performed to assess the atrophy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
2
19
0
6
Order By: Relevance
“…Several studies have demonstrated that the volume of EC seems to be more accurate than that of hippocampus for use in discriminating individuals with AD from those with MCI (de Toledo-Morrell et al, 2004;Dickerson et al, 2001;Du et al, 2001;Li et al, 2012;Pennanen et al, 2004;Varon et al, 2011). As summarized in Table 1, almost all of the study results have been similar except for the research of Killiany et al (2002) and Xu et al (2000).…”
Section: Ad Versus MCIsupporting
confidence: 62%
See 2 more Smart Citations
“…Several studies have demonstrated that the volume of EC seems to be more accurate than that of hippocampus for use in discriminating individuals with AD from those with MCI (de Toledo-Morrell et al, 2004;Dickerson et al, 2001;Du et al, 2001;Li et al, 2012;Pennanen et al, 2004;Varon et al, 2011). As summarized in Table 1, almost all of the study results have been similar except for the research of Killiany et al (2002) and Xu et al (2000).…”
Section: Ad Versus MCIsupporting
confidence: 62%
“…Most scholars chose volume measurements to evaluate the degree of atrophy in EC. Studies have found that the volume of EC is significantly reduced in patients in the following order: AD > MCI > control (Du et al, 2001(Du et al, , 2003Killiany et al, 2002;de ToledoMorrell et al, 2004;Pennanen et al, 2004;Li et al, 2012). Compared with the controls, EC was the most severely atrophied among all cortical regions studied, and it provided a high discriminating accuracy (92%) for separating patients with AD from NC subjects .…”
Section: Relationship Between Ec Atrophy and The Severity Of Admentioning
confidence: 86%
See 1 more Smart Citation
“…Atrophy of the entorhinal cortex is more accurate for making this prediction when compared to the hippocampus directly [18]. The nexus between entorhinal cortex pathology and fundamental memory impairment in AD is well established, with memory function negatively correlating with MRI measurement of entorhinal cortex atrophy [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Traditional VSRAD studies indicate that there are positive correlations between the Z-score and cognitive symptoms, which is consistent with findings of the present study. Previous research also suggests that the parahippocampal atrophy is a particularly useful index for discriminating patients with mild AD from healthy controls and is a sensitive predictor of conversion to AD [15]. It should be noted that previous VBM studies indicate that there is a correlation between AD and late-life depression [16,17].…”
Section: Discussionmentioning
confidence: 98%